1966
DOI: 10.1111/j.1151-2916.1966.tb13287.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions Between Silica and Graphite

Abstract: 24), and (26) gives, for Dv, eB K ee D v = 1 + --xD' e1 Therefore, in a chemical diffusion problem in ionic solids, one must carefully distinguish between the intrinsic vacancy diffusion coefficient, B i , a constant, and the phenomenological vacancy diffusion coefficient, Dy. By assuming some presumably realistic values for the parameters in Eqs. (23) and (27), the variation of the vacancy diffusion coefficient and the sintering flux with impurity concentration can be illustrated. Equation (23) may be written… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 11 publications
4
60
1
Order By: Relevance
“…Actually, the reactions between silica and carbon have been studied for many years because of their industrial importance, such as the production of iron, silicon, and silicon carbide. Experiments have shown that SiO 2 reacts with C to generate SiC and CO under such "metallurgic" conditions, C/SiO 2 1 (e.g., Klinger et al, 1966;Biernacki and Wotzak, 1989a). This is consistent with thermodynamic equilibrium calculations, which indicate that SiC and CO are stable at high temperatures.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Actually, the reactions between silica and carbon have been studied for many years because of their industrial importance, such as the production of iron, silicon, and silicon carbide. Experiments have shown that SiO 2 reacts with C to generate SiC and CO under such "metallurgic" conditions, C/SiO 2 1 (e.g., Klinger et al, 1966;Biernacki and Wotzak, 1989a). This is consistent with thermodynamic equilibrium calculations, which indicate that SiC and CO are stable at high temperatures.…”
Section: Introductionsupporting
confidence: 76%
“…This is consistent with thermodynamic equilibrium calculations, which indicate that SiC and CO are stable at high temperatures. The reactions under such conditions are known to proceed via solid-solid and solid-vapor reaction paths in a well-controlled and static reaction cells or furnaces (Biernacki and Wotzak, 1989b;Klinger et al, 1966). These studies show that carbon is oxidized by silica-derived oxygen.…”
Section: Introductionmentioning
confidence: 92%
“…Although reactions 8 and 9 are both favorable over the entire temperature range of interest, neither is as favorable as the direct carbon reduction of SiO (reaction 3). In addition, PSic3 is only about 1.1 Pa at 2,038 K (Klinger et al, 1966) indicating that Si(g) should not constitute a significant gaseous intermediate to overall reaction 1. As indicated, overall reaction 1 may be conveniently described by consecutive reactions (Eqs.…”
Section: (3)mentioning
confidence: 95%
“…A number of researchers (Blumenthal et al, 1966;Henderson and Tant, 1983; Kennedy and North, 1983; Kevorkijan et al, 1989Kevorkijan et al, , 1992 Khalafalla and Haas, 1972; Klinger et al, 1966; Krstic, 1992; Kurosawa et al, 1966; Kuznetsova et al, 1980; Lee et al, 1976; Lee and Cutler, 1975;Miller et al, 1979; Ono and Kurachi, 1991; Papin et al, 1972; Shimoo et al, 1990;van Dijen and Metselaar, 1991;Viscomi and Himmel, 1978;and Wei et al, 1984) have investigated the reaction kinetics of the overall carbothermal reduction reaction (Eq. 1).…”
Section: Kineticsmentioning
confidence: 97%
“…Another important parameter for the process of SiC synthesis is the time of full silica conversion into silicon carbide. Several groups have performed various kinetic studies on SiC synthesis applying different reaction conditions and carbon/silica precursors (see, for instance, [12,[14][15][16][17][18]). Although the activation energies reported varied from 230 to 550 kJ/mol, there is a general consistency that the reaction rate increases when the temperature is higher, the precursor particle size is finer, and CO is removed.…”
Section: Resultsmentioning
confidence: 99%